Local financial development and growth - Kendall, Jake (Journal of Banking & Finance, 2012)
Using unique, district-level, economic growth data, I investigate the connection between banking sector development, human capital, and economic growth in Indian districts. Disaggregate data helps avoid many of the omitted variable problems that plague similar cross-country studies. The data show districts to be financially constrained by the lack of local banking sector development, and the relationship may be non-linear. For districts in the sample, moving from the 75th percentile of credit/net domestic product to the 25th percentile implies an average loss of 4% in growth over the 1990s decade. The data also shows that human capital deepening can reduce the financial constraint. In a district at the 25th literacy percentile, the implied growth loss due to a constrained banking sector is twice as large as in a district at the 75th literacy percentile. The results are robust to the inclusion of various controls and changes in specification.